Effect of Puerarin on Osteogenic Differentiation in vitro and on New Bone Formation in vivo - Yang Y; Chen D; Li Y; Zou J; Han R; Li H; Zhang J (Dove Medical Press, 2022)
Yanran Yang,1 Daiyun Chen,2 Yilin Li,1 Jinghua Zou,1 Ruiqi Han,1 Hongkun Li,1 Jun Zhang1 1Shandong University & Shandong Key Laboratory of Oral Tissue Regeneration & Shandong Engineering Laboratory for Dental Materials and Oral Tissue Regeneration, Department of Orthodontics, School and Hospital of Stomatology, Cheeloo College of Medicine, Shandong University, Jinan, People's Republic of China; 2Department of Orthodontics, School of Stomatology, Shandong First Medical University, Jinan, People's Republic of ChinaCorrespondence: Jun Zhang, Shandong University & Shandong Key Laboratory of Oral Tissue Regeneration & Shandong Engineering Laboratory for Dental Materials and Oral Tissue Regeneration, Department of Orthodontics, School and Hospital of Stomatology, Cheeloo College of Medicine, Shandong University, Jinan, People's Republic of China, Tel +86 13953109816, Fax +86 53188382923, Email zhangj@sdu.edu.cnPurpose: Puerarin (C21H20O10) is a phytoestrogen that possesses various pharmacological effect, and several researches have revealed the relationship between puerarin and bone metabolism. This study was aimed to evaluate the potential influence of puerarin on the proliferation and osteogenic differentiation of rat bone marrow-derived mesenchymal stem cells (BMSCs) as well as on new bone formation following rapid maxillary expansion (RME) model in rats.Methods: Rat BMSCs were adopted, and the cell proliferation was detected by cell-counting kit-8 (CCK-8) assay in vitro experiments. Alkaline phosphatase (ALP) activity and alizarin red staining were analyzed quantitatively to show extracellular matrix mineralization. The mRNA and protein expression levels were used to detect osteogenic differentiation of BMSCs. In vivo bone regeneration was analyzed in a rat RME model. Eighteen 6-week-old male Wistar rats were divided into 3 groups: group 1 without any treatment, group 2 received RME and saline solution (15mg/kg), group 3 received RME and puerarin solution (15mg/kg). After 2 weeks, micro-computed tomography (Micro-CT), hematoxylin and eosin (HE) staining, and Masson staining were used to detect the new bone formation and morphological changes. Besides, ALP and bone morphogenetic protein 2 (BMP2) expression levels in mid-palatal suture were evaluated by immunohistochemical staining.Results: The results showed that puerarin upregulates cell proliferation dose-dependently. ALP activity and mineralized matrix generation were clearly enhanced at certain specific concentrations (10− 5 and 10− 6 mol/L); the expression levels of the osteoblast-related genes and proteins were increased. The measurement of micro-CT imaging revealed that puerarin significantly promoted new bone formation. Concomitantly, the histological examinations showed that puerarin solution enhanced osteogenesis in mid-palatal suture.Conclusion: Those works indicated that puerarin regulates osteogenesis in vitro and exerts a beneficial impact on bone regeneration in vivo, revealing that puerarin treatment may become one of the potential keys for improving the stability and preventing relapse of RME.Keywords: bone marrow-derived mesenchymal stem cells, bone regeneration, micro-CT, rapid maxillary expansion